Hellenostephanos. Humanist Greek in Early Modern Europe Learned Communities between Antiquity and Contemporary Culture - Päll, Janika; Volt, Ivo (Acta Societatis Morgensternianae, 2018)
The rebirth of Ancient Greek in Europe was promoted by Humanist education and ideas to such an extent that we can consider the Greek language as a formative element of Humanist culture. Next to Latin, the default common language, a Humanist has to know and use Greek, because he is not, cannot and will not be a barbarian: barbaros ou pelomai, as Julius Caesar Scaliger claimed in his verses in 1600. Wreaths (stephanoi) have been the symbols of the cult of Muses from ancient times. After the love for Greek Muses had been revived by Renaissance Humanist poets and scholars, it has remained with us both in poetic activity and in scholarship. The Hellenostephanos volume presents a collection of papers by scholars who study Humanist Greek, aspiring towards another revival of Hellenism, and trying to avoid being barbarians. The volume includes papers by Christian Gastgeber, Gita Bērziņa, Janika Päll, Charalampos Minaoglou, Erkki Sironen, Kaspar Kolk, Tua Korhonen, Johanna Akujärvi, Bartosz Awianowicz, Jean-Marie Flamand, Walther Ludwig, Alessandra Lukinovich, Martin Steinrück, Tomas Veteikis, Grigory Vorobyev, Vlado Rezar, Pieta van Beek, and Antoine Haaker.